2020
DOI: 10.3390/microorganisms8040500
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 and Mycobacterial Lipoarabinomannan as Targets of Immune Responses in Multiple Sclerosis Patients

Abstract: Interleukin 2 (IL-2) is considered a key player in exacerbating multiple sclerosis (MS). Therapies targeting its receptor have been developed; however, a resolution of the disease and side effects are still an issue of concern. The involvement of other factors, such as Mycobacterium avium subspecies paratuberculosis (MAP) and envelope protein derived from human endogenous retrovirus type W (HERV-Wenv), in MS pathogenesis has been recently suggested. Here, we investigated the levels of antibodies (Abs) directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Mycobacterium avium subspecies paratuberculosis (MAP) is accepted as the cause of Johne’s Disease (JD) [ 1 ], a chronic diarrheal wasting disease of cattle and a wasting disease in sheep and goats [ 2 ] and has long been suspected to be involved in the etiology of Crohn’s Disease (CD), an inflammatory bowel disease (IBD) of humans [ 3 ]. MAP and/or CD are also associated with many other autoimmune diseases including multiple sclerosis (MS) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], type I diabetes mellitus (T1DM) [ 14 , 15 , 16 , 17 , 18 , 19 ], rheumatoid arthritis [ 20 , 21 , 22 ], Sjogren’s syndrome [ 23 ], asymmetric lateral sclerosis [ 24 ], celiac disease [ 25 ], depression [ 26 ], thyroiditis [ 27 ], and the neurodegenerative diseases including Alzheimer’s disease [ 28 ] and Parkinson’s disease [ 29 ]. A diarrheal/wasting illness associated with infection with MAP has also been reported in non-human primates [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterium avium subspecies paratuberculosis (MAP) is accepted as the cause of Johne’s Disease (JD) [ 1 ], a chronic diarrheal wasting disease of cattle and a wasting disease in sheep and goats [ 2 ] and has long been suspected to be involved in the etiology of Crohn’s Disease (CD), an inflammatory bowel disease (IBD) of humans [ 3 ]. MAP and/or CD are also associated with many other autoimmune diseases including multiple sclerosis (MS) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], type I diabetes mellitus (T1DM) [ 14 , 15 , 16 , 17 , 18 , 19 ], rheumatoid arthritis [ 20 , 21 , 22 ], Sjogren’s syndrome [ 23 ], asymmetric lateral sclerosis [ 24 ], celiac disease [ 25 ], depression [ 26 ], thyroiditis [ 27 ], and the neurodegenerative diseases including Alzheimer’s disease [ 28 ] and Parkinson’s disease [ 29 ]. A diarrheal/wasting illness associated with infection with MAP has also been reported in non-human primates [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterium avium subspecies paratuberculosis (MAP) is accepted as the cause of Johne's Disease (JD) [1], a chronic diarrheal wasting disease of cattle and a wasting disease in sheep and goats [2] and has long been suspected to be involved in the etiology of Crohn's Disease (CD), an inflammatory bowel disease (IBD) of humans [3]. MAP and/or CD are also associated with many other autoimmune diseases including multiple sclerosis [4][5][6][7][8][9][10][11][12][13], type I diabetes mellitus [14][15][16][17][18][19], rheumatoid arthritis [20][21][22], Sjogren's syndrome [23], asymmetric lateral sclerosis [24], systemic sclerosis, celiac disease [25], depression [26], thyroiditis [27], and the neurodegenerative diseases including Alzheimer's disease [28] and Parkinson's disease [29]. A diarrheal/wasting illness associated with infection with MAP has also been reported in non-human primates [30].…”
Section: Introductionmentioning
confidence: 99%
“…Pérol L, et al have already shown the existence of anti-I autoantibodies in non-obese diabetic mice and Type 1 Diabetes patients, and the IL-2 m serve as an autoimmune target for patients with Type 1 Diabetes [97]. This is not o because IL-2 serves a role in autoimmune disease [98,99], but also due to its regulat role for Anti-inflammatory T regulatory cells (Treg) regulation, since IL-2 can control immune response by maintaining Treg cell function and promoting immune response stimulating classic T cells [100]. Importantly, the correlation between low survival a Treg infiltration in the tumor microenvironment has been well established.…”
Section: The Future Direction For Cytokine-targeted Antibody Therapymentioning
confidence: 99%